Global Geospatial Information Management: un'iniziativa delle Nazioni Unite - Salvemini, Mauro (GEOmedia, 2010)
What is Global Geospatial Information Management There is general agreement of an urgent need for an inter-government consultative mechanism that can play a leadership role in setting the agenda for the development of global geospatial information and to promote its use to address key global challenges; to liaise and coordinate among Member States, and between Member States and international organizations.